1988
DOI: 10.1111/j.1432-1033.1988.tb14264.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the amino acid sequences of the transacylase components of branched chain oxoacid dehydrogenase of Pseudomonas putida, and the pyruvate and 2‐oxoglutarate dehydrogenases of Escherichia coli

Abstract: The nucleotide sequence of bkdB, the structural gene for E2b, the transacylase component of branched-chainoxoacid dehydrogenase of Pseudornonas putida has been determined and translated into its amino acid sequence. The start of bkdB was identified from the N-terminal sequence of E2b isolated from branched-chain-oxoacid dehydrogenase of the closely related species, P. aeruginosa. The reading frame was composed of 65.5% G + C with 82.3% of the codons ending in G or C. There was no intergenic space between bkdA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 25 publications
1
8
0
2
Order By: Relevance
“…Figure 5 shows (Ho et al ., 1989), and (odpt-human) (Dah1 et al, 1987); pig (odpa-pig) (Sermon et al, 1990); mouse (odpa-mouse) (Fitzgerald et al, 1992) and (odpt-mouse) (Fitzgerald et al, 1992); rat (odba-rat) (Zhang et al, 1987), (odpt-rat) (Cullingford et a]., 1993), and (odpa-rat) (Cullingford et al, 1994); Ascarus suum (odpt-ascu) (Johnson et al, 1992) and (odpa-ascu) (Johnson et al, 1992); C. magnum (acoa-cloma) (Kruger et a]., 1994); A . eutrophus (acoaalceu) (Priefert et al, 1991); Pelobucter carbinolicus (acoa-pelca) ; K. pneumoniae (acoa-klepn) (Deng et al, 1994); bovine (odba-bovin) ; Pseudomonasputidu (odba-psepu) (Burns et al, 1988). odpa and odpt designations correspond to pyruvate dehydrogenase, whereas odba designations correspond to cy-keto acid dehydrogenase complex gene products, respectively, and the acoa designation corresponds to acetoin catabolism complexes.…”
Section: O O a I L C " T P A T T A O A T T M T~t A T~~a~m C -~A~~g K~unclassified
See 2 more Smart Citations
“…Figure 5 shows (Ho et al ., 1989), and (odpt-human) (Dah1 et al, 1987); pig (odpa-pig) (Sermon et al, 1990); mouse (odpa-mouse) (Fitzgerald et al, 1992) and (odpt-mouse) (Fitzgerald et al, 1992); rat (odba-rat) (Zhang et al, 1987), (odpt-rat) (Cullingford et a]., 1993), and (odpa-rat) (Cullingford et al, 1994); Ascarus suum (odpt-ascu) (Johnson et al, 1992) and (odpa-ascu) (Johnson et al, 1992); C. magnum (acoa-cloma) (Kruger et a]., 1994); A . eutrophus (acoaalceu) (Priefert et al, 1991); Pelobucter carbinolicus (acoa-pelca) ; K. pneumoniae (acoa-klepn) (Deng et al, 1994); bovine (odba-bovin) ; Pseudomonasputidu (odba-psepu) (Burns et al, 1988). odpa and odpt designations correspond to pyruvate dehydrogenase, whereas odba designations correspond to cy-keto acid dehydrogenase complex gene products, respectively, and the acoa designation corresponds to acetoin catabolism complexes.…”
Section: O O a I L C " T P A T T A O A T T M T~t A T~~a~m C -~A~~g K~unclassified
“…9) shows clearly that the conserved residues (reverse shading) are found in the M. capricolum sequence. Boxes shaded in grey cor- laidlawii (odpb-achla) (Wallbrandt et al, 1992); B. subtilis (odpb-bacsu) (Hemila et al, 1990) and (odbb-bacsu) (Wang et al, 1993); E. stearothermophilus (odpb-bacst) (Borges et al, 1990), human (odbb-human) (Nobukuni et al, 1990a) and (odpb-human) (Ho & Patel, 1990); bovine (odbb-bovin) (Nobukuni et al, 1990b); rat (odbb-rat) (Zhao et al, 1992); P. putida (odbb-psepu) (Burns et al, 1988); A . suum (odpb-ascu) (Wheelock et al, 1991); yeast (odpb-yeast) (Miran et al, 1993); A .…”
Section: O O a I L C " T P A T T A O A T T M T~t A T~~a~m C -~A~~g K~mentioning
confidence: 99%
See 1 more Smart Citation
“…In these systems, it was found that the genes encoding the BCDH complex were clustered in an operon. The genes encoding the BCDH complex of P. putida (bkd genes) and the PDH/BCDH dual complex of B. subtilis and Bacillus stearothermophilus are clustered in the sequence E1␣, E1␤, E2, and E3 (10,11,26,27,59). Recently, the genes for the branchedchain fatty acid-specific BCDH from B. subtilis were cloned and sequenced (64).…”
mentioning
confidence: 99%
“…E3 (10,11,26,27,59). Recently, the genes for the branchedchain fatty acid-specific BCDH from B. subtilis were cloned and sequenced (64).…”
mentioning
confidence: 99%